(3GdaQGFV GdfUjQjIs - (3GdWhSj, CHh LYaQ, fUjQ GdOjf, eMeO Hf eMeO Hf GdMSf, J (B672 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3gPg CUhd hLed ef Yde GdaQGFV hReG jJYdb HgG JYdb GdYGQV ebfGg HMSGH GdCHhGH eLJHI Yf GdJcQjQ hGdEWfGH Ydi hLg jSgd Ydi GdMGaX GdVGHW hjdhM ddcjS GdaWf (B...s
(3BNQgG (B:s
... (3hjYWj hgcPG COhG GdbQHGJ hdfhQO GdeKGd GdPj PcQg TjNfG GdEeGe GdTgjO eYjf GdOjf SGde Hf HOQGf GdeUQj aj cJGHg GdehShe HGdJMQjQ hgh eJhai (B...s
(3JHUQI GdYfhGf (B:s
(3jSei HGdJMQjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, ddRQcdj (B7/ 30s
(3GdPQjYI (B16\390s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds